Self-monitoring for improving control of blood pressure in patients with hypertension - Doogue, R; Hayes, P; Tucker, K; Fahey, T; Sheikhi, A; Koshiaris, C; Glynn, LG (Cochrane Collaboration, 2021)
This is a protocol for a Cochrane Review (intervention). The objectives are as follows: The objective of this review is to determine the effectiveness of SBPM in adults with hypertension on blood pressure control as compared to OBPM or usual care (i.e. usual care that does not include systematic use of SBPM).